Design and Building of an Automatic Water Filling System on Water Container Media Based on Arduino Esp8266 - Pradana, Alfazri Putra; Aminudin, Nur; Rizki, Fahlul; Feriyanto, Dwi (CV. Media Inti Teknologi, 2024)
In the era of rapidly developing technology, innovation is important to facilitate human life. Water is the main need for all living things, especially humans, so it needs to be managed efficiently. Water filling in reservoirs is usually still done manually, which can cause a waste of clean water. Manual water filling requires humans to control the pump as needed. However, it often happens to forget to turn off the pump after the reservoir is full, which can cause a waste of water and electrical energy. To solve this problem, the idea is to make an automatic system with Arduino ESP 8266 called